The Magnetic Urtext: Restoration as Music Interpretation - Canazza, Sergio; Schubert, Emery; Chmiel, Anthony; Pretto, Niccolò; Rodà, Antonio (Frontiers in Psychology, 2022)
This paper discusses historical-critical thought to address the problems of restoration and preservation of tape music, proposing viable solutions to the matter of digitizing the historically valuable data that exists on and is represented by magnetic tapes. A detailed program of research and restoration and some software for helping in creation of critical editions of the musical works are proposed. We also present some of the issues and controversies that must be considered and approaches we have applied in the preservation of tape music, highlighting how these interpretations can impact later performances (playback) of these tape documents. Fundamentally, we argue that the act of tape music restoration has a parallel with the interpretation of the “Urtext score” in the performance of music from the Common Practice Era.